PENGENALAN KAMISHIBAI : METODE STORY TELLING ALA JEPANG - Widiandari, Arsi; Saraswati S, Dewi; Patria, Maharani; Hastuti, Nur; Fadil, Zaki Ainul (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2017)
One of the fun methods in the process of learning and teaching Japanese  is story telling in the way Kamishibai. The person who displays kamishibai known as kamishibaiya. Kamishibai is a storytelling technique by combining images and storytelling. Characteristic of the Kamishibai method are the existence of a box containing various pictures and people who tell will draw the picture in accordance with the storyline. In the dedication for Society,  Japanese Literature Program of Cultural Sciences Faculty, Diponegoro University (FIB-UNDIP), the Japanese language teachers raised the Kamishibai method to be introduced and then applied in the environment of high school students. The event was conducted at FIB-UNDIP on October 14, 2017 with participants 20 Japanese language high school students whom residing in Semarang and other cities in Central Java. The aim of this event is to teach a new and more enjoyable method of learning Japanese that ultimately is able to improve the speaking skills and self-confidence of high school students in Japanese. In its execution, 1) Teachers provide explanations of introduction and information oabout Kamishibai's history in Japan. 2) Applying kamishibai by utilizing Kamishibai Theater so that students know the function and manner of use of Kamishibai Theater.3) Kamishibai Competition featuring all Students by choosing 1 of 2 themes (provided by teachers)  independently and 4) Evaluation. The result is the enthusiasm of the participants to show Kamishibai so high that it needs to be applied in the Japanese teaching and learning process